DONUTS AND THE GOSPEL: HOSPITALITY EVANGELISM IN AN INDONESIAN PIONEERING CHURCH - Sari Saptorini; Sukma Hendra Wahyudi Surahman (Sekolah Tinggi Teologi Duta Panisal, 2026)
Abstract: Missions focused on church planting often encounter significant challenges, including limited human resources, financial constraints, and underdeveloped social networks, all of which hinder the optimal implementation of evangelistic strategies. Previous research demonstrates that hospitality practices play an important role in strengthening religious moderation, shaping inclusive theological paradigms, and highlighting the contextual relevance of communal meals. However, existing studies generally emphasize broad concepts of hospitality and rarely examine simple strategies such as sharing popular everyday foods within the context of pioneering congregations. This study analyzes the use of donuts as a medium of hospitality evangelism in church-planting ministries and explores its relevance for evangelism, faith formation, and congregational witness. Employing a descriptive qualitative approach with a case study design, data were collected through interviews, observations, and literature analysis. The findings reveal that distributing donuts functions not merely as a social gesture but as an effective expression of hospitality that strengthens social relationships, initiates faith conversations, and reinforces the witness of pioneering congregations within a pluralistic society. The study concludes that mission strategies need not be large-scale or complex; rather, they can be embodied through simple, grounded, and contextually relevant actions that meaningfully support contemporary church ministry.